Three-dimensional numerical modeling of cryo-hydrogeological processes in a river-talik System in a continuous permafrost environment - Lemieux, Jean-Michel; Fortier, Richard; Molson, John W. H.; Liu, Weibo (Water Resources Research, 2022)
In continuous permafrost environments, understanding complex river-talik system dynamics is fundamental for the sustainable use of talik aquifers as a source of drinking water in remote communities. A conceptual model of a river-talik system was previously developed based on field investigations in the floodplain of the Kuuguluk River at Salluit, Nunavik (Quebec), Canada, including geophysical surveys and monitoring of hydraulic heads and riverbed temperatures. This conceptual model is here used to develop a 3D numerical model for simulating the governing cryo-hydrogeological processes and dynamic system behavior. The numerical simulations, supported by the field data, show that the width and thickness of the river talik is highly correlated to the width of the overlying riverbed. In summer, the river talik is hydraulically connected to the riverbed, and groundwater from the talik aquifer is contributing to river baseflow. In winter, when the river and riverbed freeze, the river talik becomes hydraulically isolated from the riverbed. Under such conditions, the river talik acts as a tube-like conduit system which focusses groundwater flow. Increasing hydraulic heads at constrictions in the talik can be sufficient to fracture the frozen riverbed and ice cover, leading to groundwater overflows and icing formation. This study presents an integrated field and modeling approach for assessing the potential of talik aquifers as reliable sources of drinking water in northern communities.